2018
DOI: 10.1038/s41427-018-0032-7
|View full text |Cite
|
Sign up to set email alerts
|

Towards sensitive terahertz detection via thermoelectric manipulation using graphene transistors

Abstract: Graphene has been highly sought after as a potential candidate for hot-electron terahertz (THz) detection benefiting from its strong photon absorption, fast carrier relaxation, and weak electron-phonon coupling. Nevertheless, to date, graphene-based thermoelectric THz photodetection is hindered by low responsivity owing to relatively low photoelectric efficiency. In this work, we provide a straightforward strategy for enhanced THz detection based on antenna-coupled CVD graphene transistors with the introductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 37 publications
(57 reference statements)
0
28
0
Order By: Relevance
“…It has been revealed that asymmetric excitation between the coupled monopoles of a Dirac cone can onset even when the bias is zero, superior than the graphene‐like ones depending solely on the peculiar design of asymmetrical coupling between the source and the gate for preferential photocurrent production. The responsivity of the PtTe 2 ‐based THz detector can reach over 1.6 A W −1 (101 V W −1 ) at 0.12 THz under zero bias voltage, much higher than previously reported graphene‐based counterpart . Furthermore, PtTe 2 integration with graphene is verified as an efficient tool to enable the self‐powered mode responsivity of 537 V W −1 at room temperature and can be further increased up to 1.4 kV W −1 at finite bias, being competitive with commercially available ones in both sensitivity and speed for fast imaging requirement.…”
mentioning
confidence: 84%
“…It has been revealed that asymmetric excitation between the coupled monopoles of a Dirac cone can onset even when the bias is zero, superior than the graphene‐like ones depending solely on the peculiar design of asymmetrical coupling between the source and the gate for preferential photocurrent production. The responsivity of the PtTe 2 ‐based THz detector can reach over 1.6 A W −1 (101 V W −1 ) at 0.12 THz under zero bias voltage, much higher than previously reported graphene‐based counterpart . Furthermore, PtTe 2 integration with graphene is verified as an efficient tool to enable the self‐powered mode responsivity of 537 V W −1 at room temperature and can be further increased up to 1.4 kV W −1 at finite bias, being competitive with commercially available ones in both sensitivity and speed for fast imaging requirement.…”
mentioning
confidence: 84%
“…For example, low-dimensional material-based photothermoelectric (PTE) detectors have successfully F I G U R E 7 Schematic of (A) graphene photothermoelectric detector device fabrication and principle of operation, Copyright 2018, Springer Nature (B) dual-output sensors based on thermoelectric effects monitoring fluid temperature and dynamics, Copyright 2018, Elsevier Ltd. All rights reserved. (C) Photo-Seebeck system under experiment (D) possible device architectures of SOTEGs, Copyright 2014, Springer Nature 15,141,286,290 pushed the response time down to the picosecond level 284 : a graphene transistor based terahertz photodetector was demonstrated with sensitivity 700 V W −1 at room temperature and 8-9 orders of magnitude faster due to hot-electron PTE effect ( Figure 7A). 141,285,286 Other examples include: propagated graphene plasmons were detected and imaged by thermoelectricity 287 ; flexibledetachable dual-output sensors of fluid temperature and dynamics with high-resolution (<0.19 K and < 0.03 cm s −1 ) was successfully synthesized 15 ( Figure 7B); a solarthermoelectric generator (SOTEG) or a dynamic piezothermoelectric generator can improve the power output by 24-158% when compared with traditional single energy conversion 288,289 ; device architecture design of SOTEG is possibly making full use of tandem solar cell 290 ( Figure 7C,D).…”
Section: Thermal Conductivity Measurementmentioning
confidence: 99%
“…For example, low‐dimensional material‐based photothermoelectric (PTE) detectors have successfully pushed the response time down to the picosecond level 284 : a graphene transistor based terahertz photodetector was demonstrated with sensitivity 700 V W −1 at room temperature and 8‐9 orders of magnitude faster due to hot‐electron PTE effect (Figure 7A). 141, 285, 286 Other examples include: propagated graphene plasmons were detected and imaged by thermoelectricity 287 ; flexible‐detachable dual‐output sensors of fluid temperature and dynamics with high‐resolution (<0.19 K and < 0.03 cm s −1 ) was successfully synthesized 15 (Figure 7B); a solar‐thermoelectric generator (SOTEG) or a dynamic piezo‐thermoelectric generator can improve the power output by 24–158% when compared with traditional single energy conversion 288,289 ; device architecture design of SOTEG is possibly making full use of tandem solar cell 290 (Figure 7C,D).…”
Section: Thermoelectric Performance Of Iva and Va Xenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Dyakonov and Shur mechanism is the main recognized mechanism for FET THz detection, additional effects may be involved in the photoresponse when a GFET is employed as a THz detector. For example, the photo-thermoelectric effect (PTE) arising from the temperature gradient in a FET can contribute to the photoresponse [ [169]]. Nevertheless, both PTE and Dyakonov and Shur mechanims exhibit a similar dependence on the gate voltage and, as result, it is challenging to discern the origin of the observed rectification [ [170]].…”
Section: mentioning
confidence: 99%